Unusual Structure, Fluxionality, and Reaction Mechanism of Carbonyl Hydrosilylation by Silyl Hydride Complex [(ArN)Mo(H)(SiH2Ph)(PMe3)3]. Issue 26 (13th May 2013) - Khalimon, Andrey Y.; Ignatov, Stanislav K.; Okhapkin, Andrey I.; Simionescu, Razvan; Kuzmina, Lyudmila G.; Howard, Judith A. K.; Nikonov, Georgii I.
Abstract The reactions of bis(borohydride) complexes [(RN)Mo(BH4)2(PMe3)2] (4: R=2, 6‐Me2C6H3; 5: R=2, 6‐iPr2C6H3) with hydrosilanes afford new silyl hydride derivatives [(RN)Mo(H)(SiR′3)(PMe3)3] (3: R=Ar, R′3=H2Ph; 8: R=Ar′, R′3=H2Ph; 9: R=Ar, R′3=(OEt)3; 10: R=Ar, R′3=HMePh). These compounds can also be conveniently prepared by reacting [(RN)Mo(H)(Cl)(PMe3)3] with one equivalent of LiBH4 in the presence of a silane. Complex 3 undergoes intramolecular and intermolecular phosphine exchange, as well as exchange between the silyl ligand and the free silane. Kinetic and DFT studies show that the intermolecular phosphine exchange occurs through the predissociation of a PMe3 group, which, surprisingly, is facilitated by the silane. The intramolecular exchange proceeds through a new non‐Bailar‐twist pathway. The silyl/silane exchange proceeds through an unusual MoVI intermediate, [(ArN)Mo(H)2(SiH2Ph)2(PMe3)2] (19). Complex 3 was found to be the catalyst of a variety of hydrosilylation reactions of carbonyl compounds (aldehydes and ketones) and nitriles, as well as of silane alcoholysis. Stoichiometric mechanistic studies of the hydrosilylation of acetone, supported by DFT calculations, suggest the operation of an unexpected mechanism, in that the silyl ligand of compound 3 plays an unusual role as a spectator ligand. The addition of acetone to compound 3 leads to the formation of [trans‐(ArN)Mo(OiPr)(SiH2Ph)(PMe3)2] (18). This latter species does not undergo the elimination of a SiO group (which corresponds to the conventional Ojima′s mechanism of hydrosilylation). Rather, complex 18 undergoes unusual reversible β‐CH activation of the isopropoxy ligand. In the hydrosilylation of benzaldehyde, the reaction proceeds through the formation of a new intermediate bis(benzaldehyde) adduct, [(ArN)Mo(η2‐PhC(O)H)2(PMe3)], which reacts further with hydrosilane through a η1‐silane complex, as studied by DFT calculations.